2017
DOI: 10.1016/j.smim.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between viruses and bacterial microbiota in cancer development

Abstract: During the last few decades we have become accustomed to the idea that viruses can cause tumors. It is much less considered and discussed, however, that most people infected with oncoviruses will never develop cancer. Therefore, the genetic and environmental factors that tip the scales from clearance of viral infection to development of cancer are currently an area of active investigation. Microbiota has recently emerged as a potentially critical factor that would affect this balance by increasing or decreasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 174 publications
(187 reference statements)
1
30
0
Order By: Relevance
“…The microbiota plays an important role controlling viral infections, such as those caused by HPV or HIV [10,[76][77][78][79]. Viral infections are responsible for approximately 15% of cancer cases worldwide and viruses that are associated with cancer include HIV, Epstein-Barr virus (EBV), Kaposi's sarcoma herpesvirus (KSHV) or human herpesvirus type 8 (HHV-8), human papillomavirus (HPV), and hepatitis B and C viruses [80].…”
Section: Cervicovaginal Microbiota and Relationship To Viral Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microbiota plays an important role controlling viral infections, such as those caused by HPV or HIV [10,[76][77][78][79]. Viral infections are responsible for approximately 15% of cancer cases worldwide and viruses that are associated with cancer include HIV, Epstein-Barr virus (EBV), Kaposi's sarcoma herpesvirus (KSHV) or human herpesvirus type 8 (HHV-8), human papillomavirus (HPV), and hepatitis B and C viruses [80].…”
Section: Cervicovaginal Microbiota and Relationship To Viral Infectionmentioning
confidence: 99%
“…Although there are several studies on the cervicovaginal microbiome and its association with viral infections, little is known about the role of microbiome on carcinogenesis and on the mechanisms responsible for HPV elimination or persistent infection. Recently, a general model of virus-bacteria-host interaction highlighting two distinct mechanisms was proposed for the contribution of microbiota to virus-associated cancers [76]. The first one suggests that the microbiota affects directly viral infectivity through generation of bioproducts that could be able to module virus-host interactions.…”
Section: Cervicovaginal Microbiota and Relationship To Viral Infectionmentioning
confidence: 99%
“…More recently, viral infections—particularly infection with human papilloma virus subtype 16—have been implicated in the increasing incidence of this group of cancers, most notably in younger adults (Chaturvedi, Engels, Anderson, & Gillison, ). Emerging hypotheses suggest that oral microbial imbalances and variations to microbial community structure may modulate viral infections by regulating host susceptibility to oncogenic viruses (Vyshenska, Lam, Shulzhenko, & Morgun, ).…”
Section: Introductionmentioning
confidence: 99%
“…(Ege et al, 2011;Farrell et al, 2012;Fujimura & Lynch, 2015;Geng et al, 2013;Greer et al, 2016;Hosgood et al, 2014;Knights et al, 2013;Marchesi et al, 2011;Shulzhenko et al, 2017;Stokholm et al, 2018;Uemura et al, 2001). Microbial communities have also been found to specifically contribute to virus induced carcinogenesis (Vyshenska et al, 2017). In particular, multiple studies confirm vaginal dysbiosis (bacterial vaginosis) to be a risk factor for HPV infection (Gillet et al, 2011) and its progression (Gillet et al, 2012;Oh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, multiple studies confirm vaginal dysbiosis (bacterial vaginosis) to be a risk factor for HPV infection (Gillet et al, 2011) and its progression (Gillet et al, 2012;Oh et al, 2015). Studies of vaginal (Champer et al, 2017) and cervical (Vyshenska et al, 2017) microbiota have found associations between changes in microbial community (e.g. overall diversity, abundances of particular taxa) and cancer development.…”
Section: Introductionmentioning
confidence: 99%